GS&E journal > Double ring bending tests on heat pretreated soda–lime silicate glass - Gregor Schwind (Challenging Glass Conference, 2020)
The strength of glass plays an important role in the dimensioning of glass components in the building industry. Here, not only parameters such as support conditions, loading rate, relative humidity etc. play an important role, but the damage by means of scratches also determines the fracture strength of glass. A heat treatment after damaging may have an influence on the resulting glass strength. The correlation between heat treatment temperature, and in particular elevated temperatures up to the glass transition temperature, and fracture stress has been studied by different researchers with several approaches of pre-treatment of specimens and test setups. This paper methodically presents various preliminary investigations which were carried out within the framework of the pre-treatment of the samples in order to investigate the influence of heat treatment of the pre-damaged samples on the fracture stress. For this purpose, double ring bending tests were performed at room temperature on pre-damaged, heat-treated soda–lime silicate glass specimens. The aim of the investigations is to obtain estimates of the extent to which a heat treatment prior to the strength test influences the fracture strength of soda–lime silicate glass. Parameters like the heat treatment temperature, the dwell time of the samples inside the furnace and the furnace design were considered. The results show that the heat treatment can increase the fracture stress of soda–lime silicate glass as float glass significant due to an assumed healing of the pre-damage during heat treatment.